Functional promoter analysis using an approach based on an in vitro evolution strategy - Remans, Tony (BioTechniques, 2005)
In vitro evolution imitates the natural evolution of genes and has been very successfully applied to the modification of coding sequences, but it has not yet been applied to promoter sequences. We propose an alternative method for functional promoter analysis by applying an in vitro evolution scheme consisting of rounds of error-prone PCR, followed by DNA shuffling and selection of mutant promoter activities. We modified the activity in embryogenic sugarcane cells of the promoter region of the "Goldfinger" isolate of banana streak virus and obtained mutant promoter sequences that showed an average mutation rate of 2.5% after applying one round of error-prone PCR and DNA shuffling. Selection and sequencing of promoter sequences with decreased or unaltered activity allowed us to rapidly map the position of one cis-acting element that influenced promoter activity in embryogenic sugarcane cells and to discover neutral mutations that did not affect promoter function. The "selective-shotgun" approach of this promoter analysis method immediately after the promoter boundaries have been defined by 5' deletion analysis dramatically reduces the labor associated with traditional "linker-scanning" deletion analysis to reveal the position of functional promoter domains. Furthermore, this method allows the entire promoter to be investigated at once, rather than selected domains or nucleotides, increasing the prospect of identifying interacting promoter regions